2022
DOI: 10.3390/e24040478
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Network Interface Flow Using a Broad Learning System Based on the Sparrow Search Algorithm

Abstract: In this paper, we propose a broad learning system based on the sparrow search algorithm. Firstly, in order to avoid the complicated manual parameter tuning process and obtain the best combination of hyperparameters, the sparrow search algorithm is used to optimize the shrinkage coefficient (r) and regularization coefficient (λ) in the broad learning system to improve the prediction accuracy of the model. Second, using the broad learning system to build a network interface flow forecasting model. The flow value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…This eventually yields ρ(at). Then, we determine the location of all updated cell state vectors which maintain the filtered values by the sigmoid activation (14), resulting in the vector Γot. Finally, ht is seen to be the final hidden state that can be calculated using Equation (16).…”
Section: Lstmmentioning
confidence: 99%
See 1 more Smart Citation
“…This eventually yields ρ(at). Then, we determine the location of all updated cell state vectors which maintain the filtered values by the sigmoid activation (14), resulting in the vector Γot. Finally, ht is seen to be the final hidden state that can be calculated using Equation (16).…”
Section: Lstmmentioning
confidence: 99%
“…Thus, the accuracy of predictive approaches was regarded as a vital factor and essential in various applications of the predictive frameworks. Reliable artificial intelligence (AI) and machine learning (ML) techniques are crucial and widely used in different applications, such as network traffic forecasts [4][5][6][7][8][9]14], the Internet of things (IoT) [10], and wireless communications [11,15]. The data characteristics indicated that the traffic used in real-time applications in current and future networks exhibited variable, nonlinear, and unstructured data formats with slowly decaying autocorrelations between different samples.…”
Section: Introductionmentioning
confidence: 99%